Post-mortem findings in southern right whales Eubalaena australis at Península Valdés, Argentina, 2003-2012 - McAloose, Denise; Rago, María Virginia; Di Martino, Matías; Chirife, Andrea; Olson, Sarah H.; Beltramino, Lucas Esteban; Pozzi, Luciana Melina; Musmeci, Luciana Raquel; la Sala, Luciano Francisco; Mohamed, Nadia; Sala, Juan Emilio; Bandieri, Lucas Martín; et al. (Diseases of Aquatic Organisms)
Between 2003 and 2012, 605 southern right whales (SRW; Eubalaena australis) were found dead along the shores of Península Valdés (PV), Argentina. These deaths included alarmingly high annual losses between 2007 and 2012, a peak number of deaths (116) in 2012, and a significant number of deaths across years in calves-of-the-year (544 of 605 [89.9%]; average = 60.4 yr-1). Postmortem examination and pathogen testing were performed on 212 whales; 208 (98.1%) were calvesof- the-year and 48.0% of these were newborns or neonates. A known or probable cause of death was established in only a small number (6.6%) of cases. These included ship strike in a juvenile and blunt trauma or lacerations (n = 5), pneumonia (n = 4), myocarditis (n = 2), meningitis (n = 1), or myocarditis and meningitis (n = 1) in calves. Ante-mortem gull parasitism was the most common gross finding. It was associated with systemic disease in a single 1-2 mo old calf. Immunohistochemical labeling for canine distemper virus, Toxoplasma gondii and Brucella spp., and PCR for cetacean morbillivirus (CeMV), influenza A, and apicomplexan protozoa were negative on formalin-fixed, paraffinembedded lung and brain samples from a subset of whales; PCR for Brucella spp. was positive in a newborn/neonate with pneumonia. Skin samples from whales with gull parasitism were PCR negative for CeMV, poxvirus, and papillomavirus. This is the first long-term study to investigate and summarize notable post-mortem findings in the PV SRW population. Consistent, significant findings within or between years to explain the majority of deaths and those in high-mortality years remain to be identified. Fil: McAloose, Denise. Wildlife Conservation Society; Estados Unidos. Southern Right Whale Health Monitoring Program; Argentina Fil: Rago, María Virginia. Southern Right Whale Health Monitoring Program; Argentina. Wildlife Conservation Society; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Di Martino, Matías. Southern Right Whale ...